A PAMPHLET IN RUSSIAN JOURNALISM - Gulshoda Husniddinova (International Engineering Journal For Research & Development, 2022)
The article covered the development of journalism in the Russian world, its peculiarities and world-famous pamphlets. It lists the reasons for the creation of pamphlets, the stages of publication. Through this, an attempt was made to reveal the true nature of the genre, as well as to reflect on the bitter fate of the authors.